2018
DOI: 10.1016/j.gie.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

A standardized imaging protocol for the endoscopic prediction of dysplasia within sessile serrated polyps (with video)

Abstract: Dysplasia within SSPs can be detected accurately by using a simple, broadly applicable endoscopic imaging protocol that allows complete resection. Independent validation of this protocol and its dissemination to the wider endoscopic community may have a significant impact on rates of interval cancer. (Clinical trial registration number: NCT03100552.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
3
28
1
1
Order By: Relevance
“…Although previous studies have reported SSA/Ps‐CD(+) in older female patients and in the proximal colon, there were no significant differences between SSA/Ps‐CD(−) and SSA/Ps‐CD(+) in this study. However, endoscopic morphological findings, such as large or small nodules on the surface and partial protrusion of the lesions, were significantly more common in SSA/Ps‐CD(+) than in SSA/Ps‐CD(−) (46.2% vs 2.7%, P < 0.01).…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Although previous studies have reported SSA/Ps‐CD(+) in older female patients and in the proximal colon, there were no significant differences between SSA/Ps‐CD(−) and SSA/Ps‐CD(+) in this study. However, endoscopic morphological findings, such as large or small nodules on the surface and partial protrusion of the lesions, were significantly more common in SSA/Ps‐CD(+) than in SSA/Ps‐CD(−) (46.2% vs 2.7%, P < 0.01).…”
Section: Discussioncontrasting
confidence: 97%
“…Tate et al reported that a demarcated area with a neoplastic pit pattern (Kudo type III/IV or NICE type II) in non-magnifying NBI observation was a useful indicator of CD within SSA/Ps, with an accuracy of 95.0%, sensitivity of 93.9%, and NPV of 98.1%. 17 However, as only SSA/Ps ≥ 8 mm were evaluated in their study, further studies are needed to determine whether this indicator can be applied to all SSA/Ps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition of dysplasia within SSP is another important concern, but it is out of the range of the present study. It requires another review article.…”
Section: Discussionmentioning
confidence: 97%